Photoelectrocatalytic conversion of urea under solar illumination using Ni decorated Ti-Fe2O3 electrodes. (10th January 2023) - Rebiai, Lamia; Muller-Bouvet, Diane; Benyahia, Raihana; Torralba, Encarnación; Viveros, Melissa Lopez; Rocher, Vincent; Azimi, Sam; Cachet-Vivier, Christine; Bastide, Stéphane
Highlights: Urea conversion with Fe2 O3 /Ni photoelectrodes as substitute for N-removal in WWTPs. Anodic photoelectrodeposition of NiOOH on n-Fe2 O3 nanorods where h + are collected. Gain of 0.5 V in urea oxidation onset potential with FTO/Ti-Fe2 O3 /Ni vs. Ni electrode. In situ light transmission recorded during CV confirms urea oxidation as EC process. Urea PEC conversion leads to N2, O2, and NO2 − ; FE ∼ 10–18% for N removal as N2 . Abstract: To reduce the energy cost and environmental impact of biological nitrogen removal in wastewater treatment plants, it would be advantageous to treat urea contained in urine at the source. In this perspective, FTO/Ti-Fe2 O3 (nanorods) photoelectrodes decorated with Ni as catalyst are developed and tested for urea photoelectrocatalytic oxidation under solar illumination. Gains up to 0.50 V in oxidation onset potential vs. metallic Ni are obtained thanks to a Ni photoelectrodeposition method. In situ transmission measurements (based on NiOOH light absorption) during electrochemical cycling allowed to evaluate the state of active Ni sites and confirmed that urea oxidation mechanism is of EC type. Photoelectrolyses give faradaic efficiencies of 10–18% and 9-35% for N2 and O2 formation, respectively. A significant and unexpected NO2 − production (∼65%) is detected indicating another or incomplete reaction pathway. The photoelectrocatalytic removal of nitrogen from urea solutions is demonstrated but requires catalysts with higher selectivity towards N2 . Graphical abstract: Image, graphical abstract